Regulation of Human Airway Epithelial Tissue Stem Cell Differentiation by β‐Catenin, P300, and CBP. (12th November 2018) - Malleske, Daniel T.; Hayes, Don; Lallier, Scott W.; Hill, Cynthia L.; Reynolds, Susan D.
Abstract: The wingless/integrase‐1 (WNT)/β‐catenin signaling pathway is active in several chronic lung diseases including idiopathic pulmonary fibrosis, asthma, and chronic obstructive pulmonary disease. Although this WNT/β‐catenin pathway activity is associated with an increase in mucus cell frequency and a decrease in ciliated cell frequency, a cause and consequence relationship between signaling and cell frequency has not been established. We previously demonstrated that genetic stabilization of β‐catenin inhibited differentiation of mouse bronchiolar tissue stem cells (TSC). This study determined the effect of β‐catenin and its co‐factors P300 (E1A‐binding protein, 300 kDa) and cAMP response element binding (CREB)‐binding protein (CBP) on human bronchial epithelial TSC differentiation to mucus and ciliated cells. We developed a modified air–liquid interface (ALI) culture system in which mucus and ciliated cell frequency is similar. These cultures were treated with the β‐catenin agonist CHIR99021 (CHIR) and antagonists to β‐catenin (XAV939), P300 (IQ1), and CBP (ICG001). We report that human TSC differentiation to mucus and ciliated cells can be divided into two stages, specification and commitment. CHIR treatment inhibited mucus and ciliated cell commitment while XAV939 treatment demonstrated that β‐catenin was necessary for mucus and ciliated cell specification. Additional studies demonstrate that a β‐catenin/P300 complex promotes mucus cell specification and that β‐catenin interacts with either P300 or CBP to inhibit ciliated cell commitment. These data indicate that activation of β‐catenin‐dependent signaling in chronic lung disease leads to changes in mucus and ciliated cell frequency and that P300 and CBP tune the β‐catenin signal to favor mucus cell differentiation.Stem Cells 2018;36:1905–12 Abstract : This study indicates that activation of β‐catenin‐dependent signaling in chronic lung disease leads to changes in mucus and ciliated cell frequency and that P300 and CBP tune the β‐catenin signal to favor mucus cell differentiation.